SERS: 'Fairy Chimney'‐Shaped Tandem Metamaterials as Double Resonance SERS Substrates (Small 4/2013). Issue 4 (15th February 2013) - Cinel, Neval A.; Bütün, Serkan; Ertaş, Gülay; Özbay, Ekmel
<x xml:space="preserve">Abstract</x> Tandem truncated nanocones resembling the 'Fairy Chimneys' rock formation in Cappadocia, Turkey, are proposed by N. A. Cinel and co‐workers to provide a highly tunable double resonance substrate for use in surface‐enhanced Raman spectroscopy. The nanocones, including two thin gold layers separated by a layer of SiO2, end up with resonances at laser excitation and Stoke's frequencies when properly designed as described on page 531. Such a tuning enables double‐resonance substrates to perform better than their single‐resonance counterparts. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>